2021
DOI: 10.3389/fphar.2021.695267
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A Novel Pharmacological Target in Diabetic Retinopathy

Abstract: Autophagy is the major catabolic pathway involved in removing and recycling damaged macromolecules and organelles and several evidences suggest that dysfunctions of this pathway contribute to the onset and progression of central and peripheral neurodegenerative diseases. Diabetic retinopathy (DR) is a serious complication of diabetes mellitus representing the main preventable cause of acquired blindness worldwide. DR has traditionally been considered as a microvascular disease, however this concept has evolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 152 publications
1
13
0
Order By: Relevance
“…Abnormal retinal autophagy has recently emerged as a frequent event in neurological disorders [ 40 ] and in preclinical and clinical DR settings [ 5 , 41 , 42 ] and has been indicated as a novel therapeutic target for DR. Particularly, in this in vivo DR model, the marker of autophagosome formation LC3 was found upregulated in diabetic retinas, as well as the marker of autophagosome–lysosome formation ATG14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal retinal autophagy has recently emerged as a frequent event in neurological disorders [ 40 ] and in preclinical and clinical DR settings [ 5 , 41 , 42 ] and has been indicated as a novel therapeutic target for DR. Particularly, in this in vivo DR model, the marker of autophagosome formation LC3 was found upregulated in diabetic retinas, as well as the marker of autophagosome–lysosome formation ATG14.…”
Section: Discussionmentioning
confidence: 99%
“…Worthy of note, BDNF deficiency in different DR cell culture models was shown to contribute to abnormally increased autophagy [ 5 ], evidenced by enhanced microtubule-associated protein light chain 3 B (LC3B) expression [ 6 ]. This is a marker of autophagosome formation [ 7 ] strictly involved in the degradation of connexin 43 (Cnx43) [ 8 ], a gap junction reduced in DR and associated to retinal vascular cell death [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Sir3 may inhibit angiogenesis in HRECs through autophagy ( 38 ). Another study by 39 showed that Müller cells stimulated by HOG-LDL had activated AMPK and increases in the levels of the autophagy-related proteins ATG-5, Beclin-1, and LC3II/LC3I and the expression of the apoptosis-related protein caspase-3. This finding suggests that autophagy activation can lead to apoptosis.…”
Section: Autophagy Diabetes and Diabetic Complicationsmentioning
confidence: 99%
“…Cell death (through apoptosis, necrosis, and autophagy) can be induced by reactive oxygen species (ROS) and inflammatory cytokines (ILs) secreted in response to hyperglycemia (Volpe et al, 2018). As a result, retinal impairment is associated with autophagy activity in diabetic patients (Adornetto et al, 2021). In fact, the onset and development of ARMD has been attributed to the dysfunction of autophagy of RPE cells.…”
Section: Autophagy In Other Eye Diseasesmentioning
confidence: 99%